Financial Statement: Language View Points using Genre analysis - Asri, Marselinus (Journal of Economics and Management, 2023)
This research article examines accounting statements from the perspective of genre analysis and language usage. By applying genre theory and linguistic analysis, we aim to explore the various language viewpoints employed in the construction of accounting statements and their implications for financial communication. Through a comprehensive review of relevant literature and a qualitative analysis of a sample of accounting statements from several Europe countries, US, Asia and Africa, we identify and categorize different genres within the accounting domain. We investigate how the choice of language structures, lexicon, and rhetorical devices within these genres influence the representation of financial information and shape the perceptions of stakeholders. In addition, we investigate the potential impact of linguistic differences in accounting statements on information transparency, correctness, and comprehensibility. The study's findings contribute to a better understanding of the relationship between language and accounting procedures, giving light on the function of genre analysis in improving financial reporting efficacy and encouraging communication efficiency in the accounting industry.